Improving the students' reading comprehension through Numbered Heads Together technique - Suud Purnomo (Universitas Islam Negeri Palangka Raya, Indonesia, 2012)
The method applied in this research was a classroom action research. After three cycles consisting of two meetings each were conducted, the appropriate model of NHT technique in teaching reading encompassed the following steps: (1) leading students to the topic by giving some questions and/or showing a picture(s), (2) connecting the topic with the students